2018
DOI: 10.1108/mf-05-2017-0188
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing accountability of the cash waqf (endowment) institution in Indonesia

Abstract: Purpose The purpose of this paper is to reconstruct the accountability of the cash waqf institution in Indonesia, including the logic which may refer to the accountability objective. Design/methodology/approach The paper employs the qualitative method with a constructivist paradigm. Four different characteristics of cash waqf institutions in Indonesia serve as the object of this research with other related respondents, such as the government and Islamic banks. These multiple case studies may represent the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…According to Siswantoro et al (2018) accountability in an Islamic perspective is a responsibility between Muslim / Islamic organizations and their stakeholders. By using this perspective, accountability in Islamic entities will have higher ethical considerations than non-Islamic entities (Kamaruddin & Auzair, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Siswantoro et al (2018) accountability in an Islamic perspective is a responsibility between Muslim / Islamic organizations and their stakeholders. By using this perspective, accountability in Islamic entities will have higher ethical considerations than non-Islamic entities (Kamaruddin & Auzair, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are a wide range of research addressing cash Waqf. Previous studies mainly attempted to associate Cash Waqf with microfinance (Zabri and Mohammed, 2018), small-and medium-sized enterprises (Amuda, Embi, & Babatunde 2014), education (Aziz, Johari, & Yusof, 2013), factors influence the contributors (Witjaksono, 2018) , management (Siswantoro, Rosdiana, and Fathurahman, 2018), E-cash Waqf (Yusof et al, 2014), and socio-economics development (Sanusi and Shafiai, 2015). Atan and Johari (2017) aim to examine the 2006-2016 literature of Waqf dealing with the topic poverty alleviation; the writers concentrate on the publications' years, the number of the contributors, and the country of a study.…”
Section: Previous Studiesmentioning
confidence: 99%
“…As hundreds of studies they confirmed that Waqf is an efficient method to alleviate poverty. On the other hand, the contemporary scholars are focusing on maximizing the benefits of cash waqf, for example Nadya, Alwyni, Hadiyati, & Iqbal (2019); while others concentrate on the Waqf manager accountability (Siswantoro et al, 2018).…”
Section: Previous Studiesmentioning
confidence: 99%
“…On the other hand, the effectiveness of Waqf is also related to the idea of accountability (Arshad & Zain, 2017;Mansor & Jamil, 2018). As reported by Noordin et al (2017); Siswantoro, Rosdiana, and Fathurahman (2017); Yaacob, Petra, and Sumardi (2015), accountability is highly discussed and highlighted among scholars in ensuring that Waqf institutions are operated based on integrity and trust (Yaacob et al, 2015). Furthermore, the report by audit department showed that management of Waqf property in Peninsular Malaysia is still not satisfied, leading to the increase in queries and doubts the effectiveness and efficiency of this institution in handling Waqf properties (Jabatan Audit Negara, 2017).…”
Section: Empirical Study and Indicators Of Effectiveness In Waqf Institutionmentioning
confidence: 99%